Studying Fraud as White Collar Crime - Smith, Geoff (Palgrave Macmillan, 2011)
"Despite efforts to tackle fraud and white collar crime, they still thrive in our society. This book explores the themes, theories and issues that are essential for understanding these crimes, using extensive examples drawn from recent events. This is an ideal guide to the changing landscape of fraud for students of Criminology and Sociology"--